Analisis Pengaruh Fear of Marriage terhadap Intensi Penundaan Pernikahan Generasi Z di Kota Semarang - Deanita Bella; Nadia Itona Siregar (Jurnal Penelitian Sosial Ilmu Komunikasi, 2026)
The development of information technology has made Generation Z in Indonesia a group highly vulnerable to exposure to digital content. In the virtual public space, the rise of the "Marriage is Scary" narrative trend triggers the phenomenon of fear of marriage (gamophobia), characterized by extreme anxiety toward financial responsibilities and emotional risks post-marriage. This condition is closely related to the sharp decline in marriage rates, including in the city of Semarang. This study aims to analyze the influence of fear of marriage on the intention to delay marriage among Generation Z in Semarang City. The research method used is quantitative with a survey approach. The research population focuses on Generation Z aged 20-29 years in the city of Semarang, with a total population of 257,078 individuals and a sample of 100 respondents taken using a purposive sampling technique. Primary data was collected through the technique of distributing questionnaires to respondents who are part of Generation Z in the city of Semarang. Meanwhile, secondary data were obtained using the literature study technique. Data analysis was conducted using simple linear regression analysis with the aid of IBM SPSS software version 25. The results of this study show a significance value of 0.000 (< 0.05) with a regression coefficient (B) of 0.340. The coefficient of determination (R2) value of 0.132 indicates that fear of marriage can explain 13.2% of the variation in the intention to postpone marriage. Thus, the higher the fear of marriage an individual has, the greater their tendency to postpone marriage.